Direct Kurdish features in the plays of (Muhyiddin Zangana) - غريب, هاوژين عبدالخالق; أحمد, فائق مصطفى (Sulaimani Journal for Humanities, 2019)
The author and play-writer (Muhealdin Zangana) was famous for his inimitably simple style, through which he was able to express the issues of his community, which formed an enormous part of his life, his productions varied between stories, novels and plays; however, he was a special in his plays. These plays were not just stories and personalities, but went beyond the limits of reality and entered an immense world of the writer's imagination to express individuals belonging to an oppressed society who suffered from oppression and have been deprived of its most basic rights. The most important of these is the right to self-determination. In his plays, Zangana plays reflected on several social and humanitarian issues, the most important of which is the status of the Kurdish individual in a society seen as a second-class citizen. Through his plays (the Vision of the King, a Prayer of Norouz, the Safety Evening to You the White Negroes, and the Greenness of the Logs), Zangana could demonstrate his idea throughKurdish names and figures, repeating the Kurdish images in his plays including Kurdish regions and mountains, confirming Zangana's belonging to this society which went through all difficulties in order to achieve and realize itself, this research tries particularly to focus on those features related to the Kurds, especially the features that dealt with the Kurds directly. The titles of these plays points to an idea related to the Kurdish people both in history and culture. It deals with the character of Zuhak and Blacksmith Kawa, where both form an important stage in the history of this people; moreover it deals with the Kurds and their ancestors through the play "The Vision of the King". This evidence on Zangana's attachment to this people.